EXPERIMENTAL INVESTIGATION OF CREEP BEHAVIOUR OF SATURATED SOFT CLAY SUBJECTED STATIC LOADING - Nguyen, Ngoc Thang (GEOMATE Journal, 2023)
Creep of clayey soils is defined as the time-dependent deformation under sustained stresses, due to viscous behavior of the soil skeletons. The creep behavior of soil is influenced by several main factors, such as time, temperature, soil type, soil structure, stress history, stress state, and drainage conditions. Soft foundations of low embankments exhibit significant time-dependent effect on deformation in decades after construction, and there is a lack of simple method for predicting the creep rate of over-consolidated soft clay under plain strain condition. In this study, plane strain triaxial test have been conducted to investigation volumetric, axial and lateral creep strain of saturated soft clay. The experimental results show that the volumetric creep strain of soil specimens subjected to static loading increases with the increasing magnitude of external load, and it depends on the amplitude of pre-consolidation load, a larger pre-consolidation load value is associated with a significantly reduced volumetric creep strain. The variation of axial strain and lateral strain are similar with variation of volumetric creep strain for both normally and over-consolidated state, but the rate of variation decreases significantly when the soil transitions into an over-consolidated state. In addition, the test results show that the excess pore pressure develops and increases rapidly to reach the peak values as soon as the external loads was applied on the specimen and then decreases gradually to a stable value of zero during creep deformation stage of soil.